The Importance of Training Needs’ Questionnaire in order to Arrange Science Teacher Training Program (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2017)
An ideal teacher training program is by participant’s need. The major aim of this study is getting information about science teacher’s perception and needs in their professional’s life as a science teacher in Junior High School. The main idea of teacher training is to strengthen the integrated science of Natural Science concepts and problem-based learning. Data is gathered by spreading training needs questionnaire to 20 science teachers under an education foundation in Bandung. The questionnaire consists of six main parts which are teacher’s profile, teacher’s training, integrated science, problem-based learning, environmental problem and lesson preparation. The result of the training needs questionnaire is used as a basic of Science Teacher Training Program’s Arrangement. There are four significant findings in training needs questionnaire. The first finding, the method of training is important. Most of the participant choose discussion method with sharing. The second finding, webbed model/ thematic approach in integrated science is unfamiliar for the participant. Therefore, the thematic approach can be a potential material for teacher training program. The third finding, 70% participants find obstacles in problem-based learning. This finding shows that the need to put problem-based learning material in teacher training program. The fourth finding, 65% participant, express opinions that material about lesson preparation is critical in teacher training. Based on the explanation above, we can conclude that training program for science teacher needs to be arranged according to teacher needs. So, the training program should use discussion method with sharing. Material about the thematic approach, problem-based learning and learning preparation are very potential to put into a training program for Junior High School science teacher.